Hyperbaric Oxygen Improves Cognitive Impairment Induced by Hypoxia via Upregulating the Expression of Oleic Acid and MBOAT2 of Mice - Zhen Li; Jun Fu; Kaiyuan Jiang; Jie Gao; Yuejun Guo; Chen Li; Liangcai Zhao; Jutaek Nam; Hongchang Gao (Antioxidants)
Cognitive impairment (CI) causes severe impairment of brain function and quality of life of patients, which brings a great burden to society. Cerebral hypoxia is an important factor in the pathogenesis of CI. Hyperbaric oxygen (HBO) therapy may mitigate hypoxia-induced CI, but its efficacy and mechanisms are not fully understood. In this study, a mice model of CI induced by hypoxia environment was established, then behavioral tests, pathological examination, metabolomic and lipidomic analyses, and molecular biology were used to assess the impact of HBO on hypoxia-induced CI. HBO was found to alleviate CI and pathological damage of hypoxia mice. Metabolomic, lipidomic, and molecular biology analyses showed that HBO increased the levels of oleic acid (OA) and membrane-bound O-acyltransferase 2 (MBOAT2), thereby altering the composition of membrane phospholipids (PLs) and reducing hypoxia-induced neuronal ferroptosis (FPT) to interfere with cognitive function in mice. In vitro experiments confirmed that OA and MBOAT2 led to membrane PL remodeling in a mutually dependent manner, affecting cell resistance to hypoxia-FPT. The results emphasized the combined effect value of OA and MBOAT2 in HBO for hypoxia-induced CI, and provided a novel perspective for the treatment of CI by HBO.